GLOBALISATION, RESOURCE WEALTH, AND THE ENVIRONMENTAL KUZNETS CURVE: PATHWAYS TOWARD SUSTAINABLE GROWTH IN ARCTIC ECONOMIES - Taiwo A Muritala (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Sustainable growth in emerging economies depends largely on relationships between financial advancement, globalization, utilization of resources and environment quality. The paper employed the Dynamic panel System GMM estimation with robustness checks (2SLS) to examine the associations among financial development, energy consumption, natural resource rents, globalization, economic growth, and CO 2 emission by using a balanced panel consisting of 8 emerging economies, from 2015 to 2023). The study revealed that financial development contributes tremendously to economic growth with no direct impact on the quality of environment, although energy consumption contributes both to economic growth and environmental degradation. The positive impacts of natural resource rents are obviously an improved quality of the environment, which denotes enhanced governance, and globalization plays a significant role in enhancing growth, with no direct impact on the environment. The EKC hypotheses is also affirmed (negative squared term of GDP), implying higher levels of income result in decreasing environmental degradation. The paper suggest some policy implications on integration of green finance, green energy transition, management of resources, development of globalization strategies in line with environmental goals. Future studies are necessary to further increase the geographic and time dimensions and study sector and institutional-specific dynamics.